Computational study of the effect of pump mounting to foundation compliance on pump natural frequencies. Issue 1 (January 2021) - Yashchenko, A; Verbovyi, A; Rudenko, A
Abstract: This article deals with the development of more accurate models of high-performance pump machines, which are mounted onto the foundation by means of compliant supports. These models demonstrate dependence between support foundation compliance and dynamics of pump elements such as rotor, pump casing and casing of pump bearings. After application of these approaches, the method of vibrational calculation with variable values of support compliance taken into account is provided. This task has been performed by using the multifunctional program complex ANSYS Workbench. In particular, the investigation employs the Modal Analysis subprogram, which implements the finite element method at the tasks of vibration analysis of constructions. The degree of effect of pump baseplate compliance on the rotor dynamics behaviour has been determined. Data charts of dependencies of rotor, pump casing and bearing housings natural frequencies on pump mounting to foundation compliance have been obtained.